Resistance Movement in Estonia in 1955–1985 - Niitsoo, Viktor (Genocidas ir rezistencija, 1997)
After the Soviet Union occupied and annexed Estonia in June 1940, the Estonian people immediately began to resist foreign rule, which lasted until Estonia regained its independence in August 1991. Initially, it was a passive resistance to the Soviet transformation of Estonia and an attempt to preserve national values. Active resistance began as soon as the conditions were right. When hostilities broke out between Germany and the Soviet Union, many men retreated into the forests, took to arms and began to fight against retreating German troops, destruction battalions and the red army. Under the Soviet totalitarian regime, active resistance could not be massive. With few exceptions (youth demonstrations in 1980), there were no outbreaks of generalised resistance in Estonia until the late 1980s, unlike it was the case in Hungary in 1956, Czechoslovakia in 1968 and Poland in 1956, 1968, 1976 and 1980.